im a seventh grader taking 8th grade math and my teacher didn't have time to fluently explain this to us so I am completely lost some one help please!

1. Start by expanding the expression contained in the parentheses () on the left hand side

5 + 11(2-m) = m - 9 ⇒ 5 +

**22 - 11m**= m - 92. Bring all the terms with m to the right hand side, and all the other terms to the left hand side

5 + 22 - 11m = m - 9 ⇒ 5 + 22

**+ 9**= m**+ 11m**3. Add and simplify both sides of the equation

5 + 22 + 9 = m + 11m ⇒

**36**=**12m**4. Divide both sides of the equation by 12

36 = 12m ⇒

**3**=**m**The final answer is m=3.